Birth weight and prepubertal body size predict menarcheal age in India, Peru, and Vietnam. Issue 1 (28th September 2017) - Aurino, Elisabetta; Schott, Whitney; Penny, Mary E.; Behrman, Jere R.
Abstract: Evidence on the associations of birth weight and prepubertal nutritional status with menarcheal age for low‐ and middle‐income countries is limited. We investigated these relationships using the Young Lives younger cohort for 2001 Indian, Peruvian, and Vietnamese girls born in 2001–2002. Girls were followed at approximately ages 1, 5, 8, and 12 years. Weibull survival models estimated hazards of earlier menarche on the basis of birth weight Z‐scores (BWZ), and age‐8 BMI‐for‐age Z‐scores (BMIZ) and height‐for‐age Z‐scores (HAZ). Estimates controlled for potential individual‐, mother‐, and household‐level confounders and for changes in anthropometry between 1 and 8 years. In adjusted models, BWZ predicted later age at menarche (hazard ratio (HR) = 0.90, 95% CI: 0.83–0.97). Conversely, HAZ (HR = 1.66, 95% CI 1.5–1.83) and BMIZ at 8 years (HR = 1.28, 95% CI: 1.18–1.38) predicted earlier menarche. Changes in HAZ and BMIZ between 1 and 8 years were not associated with earlier menarche. Associations were consistent across countries, though with variation in estimated magnitudes. Maternal height and age were associated with later menarche. This evidence points to consistently robust and opposite associations of birth weight versus prepubertal attained height and body mass index with menarcheal age in three diverse settings with regard to nutrition, ethnicity, and socioeconomic status.